2004
DOI: 10.1074/jbc.m408461200
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Peroxisome Proliferator-activated Receptor γ Agonists and Tumor Necrosis Factor α on Adipocyte ApoE Expression

Abstract: ApoE is expressed in multiple mammalian cell types in which it supports cellular differentiated function. In this report we demonstrate that apoE expression in adipocytes is regulated by factors involved in modulating systemic insulin sensitivity. Systemic treatment with pioglitazone increased systemic insulin sensitivity and increased apoE mRNA levels in adipose tissue by 2-3-fold. Treatment of cultured 3T3-L1 adipocytes with ciglitazone increased apoE mRNA levels by 2-4-fold in a dose-dependent manner and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 54 publications
1
62
1
Order By: Relevance
“…28,29 PPARa also regulates the expression of lipoprotein receptors and cholesterol transporters, as apolipoprotein E (ApoE), that contains a PPRE sequence on its promoter. 39 Intriguingly, ApoE over-expression has been documented in normal MS 33 and in prostate CSCs. 14 We here observed that ApoE gene is over-expressed in T-MS compared with N-MS, and that ApoE expression is regulated by PPRAa expression in MCF7-MS (Supplementary Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 PPARa also regulates the expression of lipoprotein receptors and cholesterol transporters, as apolipoprotein E (ApoE), that contains a PPRE sequence on its promoter. 39 Intriguingly, ApoE over-expression has been documented in normal MS 33 and in prostate CSCs. 14 We here observed that ApoE gene is over-expressed in T-MS compared with N-MS, and that ApoE expression is regulated by PPRAa expression in MCF7-MS (Supplementary Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The dose-related increase with rosiglitazone establishes the apoE response after treatment of adipocytes with three different PPAR␥ agonists, rosiglitazone (Fig. 1A), ciglitazone, and pioglitazone (4,6). The time course for the response of the apoE gene to treatment with rosiglitazone ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Treating isolated adipocytes or intact humans with PPAR␥ agonists increases adipocyte and adipose tissue apoE gene expression (4,6). The proinflammatory cytokine, tumor necrosis factor-␣, reduces adipocyte apoE expression, an effect mediated by the NF-B transcriptional complex binding an element in the apoE gene proximal promoter (4,7). Reactive oxygen species produced by the stromovascular fraction of adipose tissue harvested from obese mice also reduce adipocyte apoE expression via the NF-B pathway (8).…”
Section: Ppar␥mentioning
confidence: 99%
See 2 more Smart Citations